Pengetahuan dan Sikap Petani tentang Alat Pelindung Diri dalam Penggunaan Pestisida di Desa Darungan Kecamatan Patrang Kabupaten Jember - Nur Jannah; Nurfika Asmaningrum; Kholid Rosyidi Muhammad Nur (Pustaka Kesehatan, 2023)
The use of pesticides has a negative impact on humans because pesticides can enter the human body through absorption from the skin, intentional oral or inhalation. Knowledge related personal protective equipment from work accident is very important so that it does not interfere with the farmers’ work activities and does not interfere with the health of farmers. Personal protection that can be used is by using complete Occupational Health and Safety including masks, gloves, hats and special clothes. The positive attitude of farmers is needed so that farmers are aware and willing to wear personal protective equipment as a form of prevention of work accidents. The purpose of this study was to examine the knowledge and attitudes of farmers regarding personal protective equipment in the use of pesticides in Darungan Village, Patrang District, Jember Regency. This research is a descriptive study on a total sampling of 100 farm workers. The results showed that most of the respondents (93%) had worked > 5 years. The majority of farmers' level of knowledge about personal protective equipment is still low (86℅), 69℅ of farmers have a positive attitude.